A facile method to fabricate functionally integrated devices for oil/water separation. Issue 10 (16th February 2015) - An, Qi; Zhang, Yihe; Lv, Kaikai; Luan, Xinglong; Zhang, Qian; Shi, Feng
Abstract : In this paper, we present a facile method for the fabrication of a functionally integrated device, which has the multi-functions of the oil-containment boom, oil-sorption material, and water/oil-separating film, through a single immersion step in an ethanol solution of stearic acid. Abstract : In this paper, we present a facile method for the fabrication of a functionally integrated device, which has the multi-functions of the oil-containment boom, oil-sorption material, and water/oil-separating film, through a single immersion step in an ethanol solution of stearic acid. During the simple immersion process, the two dominant factors of superhydrophobicity, surface roughness and low-surface-energy coatings, could be accomplished simultaneously. The as-prepared functionally integrated device with superhydrophobicity/superoleophilicity displayed a lower density than that of water, such that it could float on water and act as an oil-containment boom; an efficient oil-absorbing property, which was attributed to the capillary effect caused by micrometer-sized pore structures and could be used as oil-sorption materials; a high oil/water separating efficiency which was suitable for water/oil-separating film. In this way, the functions of oil collection, absorption, and water/oil separation are integrated into a single device, and these functions could work independently, reducing the cost in terms of energy consumption and being versatile for a wide range of applications.